A baixa frutificação natural e os mecanismos envolvidos na reprodução de orquídeas polinizadas por engano - Maciel, Artur Antunes (2016)
Deceptive pollination is characterized by the pollen transfer by a pollinator without any reward This antagonistic interaction is present in 7,500 species of angiosperms and has considerable evolutionary stability. As a result of deception and learning ability of pollinators, these plants have low reproductive rates and often present auxiliary mechanisms. This study aimed to describe the reproductive biology of two rewardless species, and to assess the existence and importance of autogamous mechanisms in their reproduction. In addition, it evaluated the effects of florivory and rain fall on the longevity of flowers and fruit set in a greenhouse experiment. The research was conducted with Cyrtopodium hatschbachii and C. paludicolum occurring in Uberlândia, Minas Gerais, Brazil. The results showed that both are self-fertile and non-autogamous species, i.e. have no mechanism for apomictic reproduction or spontaneous autogamy. The two had only one species of pollinator bees belonging to the Centridini tribe and had extremely low fruit set rates and reproductive success. Only Cyrtopodium hatschbachii was capable of producing fruits after rain-assisted pollination, which comprised about 10% of the fruits. In addition, for this species it was recorded in a greenhouse experiment that precipitation and florivory reduced the longevity of flowers. However, when assessing the interaction between these two effects, we found a new mechanism of pollination, a form of autogamy mediated by rain and enhanced by floral herbivory. This phenomenon was responsible for conversion of 18.9% of the flowers into fruits, which can be even higher under natural conditions. This highlights the importance of including, in all the factors and interactions that can somehow affect reproduction in studies evaluating the reproductive sucess of the plants.